1966
DOI: 10.1017/s0025315400017641
|View full text |Cite
|
Sign up to set email alerts
|

Persistent, vertical-migration rhythms in benthic microflora.: II. Field and Laboratory Studies On Diatoms From The Banks Of The River Avon

Abstract: The vertical migration of two Euglena species and several diatom species into and out of the sediment on the banks of the River Avon has been studied under natural conditions. All species have been shown to migrate vertically upwards when exposed during daylight. Tidal flooding of the sediment is generally preceded by re-burrowing of the algae beneath the surface. Methods have been devised to follow these migrations in both the field and laboratory. Laboratory experiments show that these migrations are rhythmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
91
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(100 citation statements)
references
References 13 publications
9
91
0
Order By: Relevance
“…In favourable conditions (such as low light) at time t i , microalgae continue to accumulate in the surficial layers, reaching maximum concentrations typically within 1-2 h. This finding apparently agrees with the results of Round & Palmer (1966) who reported that a 2-h period of light exposure was required before biofilm formation. The acceleration often observed in surface biomass accumulation when the light was switched on (e.g.…”
Section: Biofilm Formationsupporting
confidence: 90%
“…In favourable conditions (such as low light) at time t i , microalgae continue to accumulate in the surficial layers, reaching maximum concentrations typically within 1-2 h. This finding apparently agrees with the results of Round & Palmer (1966) who reported that a 2-h period of light exposure was required before biofilm formation. The acceleration often observed in surface biomass accumulation when the light was switched on (e.g.…”
Section: Biofilm Formationsupporting
confidence: 90%
“…This is in agreement with the general observation that a minimum of light exposure is required for microalgae to move upwards (Round & Palmer 1966, Consalvey et al 2004b, Mitbavkar & Anil 2004.…”
Section: Variability In the Migration Pattern And Biofilm Constitutionsupporting
confidence: 92%
“…Sequential patterns of migration of species to and from the surface have been seen in other studies from a range of different habitats (Round and Palmer 1966;Kingston 1999;Brotas et al 2003). There is also good evidence that microphytobenthic biofilms develop vertical structure with surface and subsurface layers of different taxa (Paterson et al 1998).…”
Section: Discussionmentioning
confidence: 61%